Studying the effect of boiler water releasing in rivers on some water properties (Al-Euphrates River at Al-Mussaib thermal power station as case study)' - Mohsin J. Nasir; Ahmed Sami Naser; Wisam Abdulabbas Abidalla; Ghosoon Natiq Ismael (Water Practice and Technology, 2023)
Studying the effect of boiler water released in rivers on some water properties such as density, viscosity was done in this research. Equations of momentum, conversation, turbulence and energy were used with the relation between the temperature and water properties to describe those properties along the study reach. Simplifying of partial equation was done to obtain system of linear equation. Verification of numerical model by conducting comparison of observed data from Euphrates River at Mussaib Thermal Power Station with those computed by the model. The comparison results of density and viscosity show an agreement with using statistical tests such as Chi square and RMSE. The results of the study showed that increasing the bed roughness from 0.04 m to 0.12 m causes a longitudinal retardation of the values of density and viscosity values about (26 and 22%) respectively and vertical advance of these values about (14 and 12% ) respectively. Increasing the water surface slope from (6 cm/km to 12 cm/km) causes a longitudinal advance of density and viscosity values about (19 and 12%) respectively and vertical retardation of these values about (16 and 13%) respectively. HIGHLIGHTS Effects of boiler water on water river properties such as water density and water viscosity were studied.; Significance and degree of freedom between observed data from the river and predicted data from the model were studied.; The effects of hydraulic river properties such as bed height and water surface slope on distribution of the values of these water river properties were explored.;